2012
DOI: 10.1007/s10815-012-9801-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of DNA integrity analysis in idiopathic recurrent pregnancy loss following spontaneous conception

Abstract: Purpose Standard semen parameters are poor predictors of fertility potential. To date, apart from, paternal karyotyping sperm factors are not evaluated in recurrent pregnancy loss (RPL), only recent studies have emphasized the role of sperm factors in early embryonic development as sperm transcribes genes critical for early embryonic development. Sperm DNA integrity is useful diagnostic and prognostic marker and has clinical implications in idiopathic recurrent pregnancy loss (iRPL) following spontaneous conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 50 publications
1
54
0
5
Order By: Relevance
“…The deleterious effect of fragmented paternal DNA on embryonic viability and progression of pregnancy has been experimentally shown in mouse models [Ahmadi and Ng 1999] and similar results were also observed in human patients who opt for assisted reproductive technologies such as IVF and ICSI [Lin et al 2008;Muriel et al 2006;Robinson et al 2012;Tandara et al 2014;Tesarik et al 2004;Wdowiak et al 2015;Zhao et al 2014;Zini et al 2008]. In idiopathic cases of recurrent miscarriages too, the higher rates of sperm DNA fragmentation have been implicated, in the absence of any detectable female factor abnormality [Absalan et al 2012;Brahem et al 2011;Carrell et al 2003;Kumar et al 2012;Ramasamy et al 2015;Ribas-Maynou et al 2012;Zidi-Jrah et al 2016]. In congruence, studies have also reported interrelations between sperm chromatin alterations and early embryo post-implantation development in couples undergoing ART [ (Borini et al 2006;Seli et al 2004].…”
Section: Introductionmentioning
confidence: 58%
“…The deleterious effect of fragmented paternal DNA on embryonic viability and progression of pregnancy has been experimentally shown in mouse models [Ahmadi and Ng 1999] and similar results were also observed in human patients who opt for assisted reproductive technologies such as IVF and ICSI [Lin et al 2008;Muriel et al 2006;Robinson et al 2012;Tandara et al 2014;Tesarik et al 2004;Wdowiak et al 2015;Zhao et al 2014;Zini et al 2008]. In idiopathic cases of recurrent miscarriages too, the higher rates of sperm DNA fragmentation have been implicated, in the absence of any detectable female factor abnormality [Absalan et al 2012;Brahem et al 2011;Carrell et al 2003;Kumar et al 2012;Ramasamy et al 2015;Ribas-Maynou et al 2012;Zidi-Jrah et al 2016]. In congruence, studies have also reported interrelations between sperm chromatin alterations and early embryo post-implantation development in couples undergoing ART [ (Borini et al 2006;Seli et al 2004].…”
Section: Introductionmentioning
confidence: 58%
“…Sperm DNA integrity is important for successful fertilization and normal embryonic development, as evidenced by sperm with poor DNA integrity being negatively correlated with successful pregnancies 36 - 40 . Furthermore, sperm oxidative stress correlated with decreased sperm motility, increased sperm DNA damage, decreased acrosome reaction and lower embryo implantation rates following IVF 41 - 43 .…”
Section: Male Obesity On Sperm Dna Integrity and Oxidative Stressmentioning
confidence: 99%
“…The chromatin in mammalian sperm can broadly be divided into three major structural domains: (1) the vast majority of sperm DNA is coiled into toroids by protamines, (2) a much smaller percent (5-15%) remains bound to histones and thus retains its nucleosomal structure, and (3) DNA that is attached to the sperm nuclear matrix at MARs (matrix attachment regions) at intermediate intervals of approximately 50 kb throughout the genome (9). Sperm chromatin is essential for sperm function and subsequent embryonic development; defects in sperm chromatin have been linked to natural reproductive malfunctions, such as spontaneous abortion and assisted reproductive failure (10-12). These defects can include disrupted DNA integrity, which may affect fecundity and embryo growth, leading to embryo loss (13-15).…”
Section: Sperm Genetic Factorsmentioning
confidence: 99%